2020
DOI: 10.4155/fmc-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Malaria transmission-blocking Drugs: Implications and Future Perspectives

Abstract: Since the world is inching toward malaria elimination, the scientific community worldwide has begun to realize the importance of malaria transmission-blocking interventions. The onus of breaking the life cycle of the human malaria parasite Plasmodium falciparum predominantly rests upon transmission-blocking drugs because of emerging resistance to commonly used schizonticides and insecticides. This third part of our review series on malaria transmission-blocking entails transmission-blocking potential of precli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 178 publications
0
7
0
Order By: Relevance
“…The antimalarial potential of Rh has been previously reported. 39 , 40 In this regard, the combination that showed a better Plasmodium inhibitory performance with an IC50 of 2.5 μg/mL, DHP(G2)-MPA-Rh/hep, required a w DHP / w heparin ratio 20:1 to establish the complexes, which led to a larger amount of Rh in the sample than in the cases of DHP(G3)-MPA-Rh/hep or DHP(G4)-MPA-Rh/hep, whose respective complexation ratios were 7.5:1 and 4:1 and their IC50 was higher than 12 μg/mL. Surprisingly, the antiparasitic activities of DHP(Gn)-GMPA-Rh complexes with heparin (IC50 between 4.7 and 5.1 μg/mL) were slightly better but did not differ too much from those of the homologues without the fluorophore ( Figure 6 a), even though the ratios of complexation ( w DHP / w heparin 15:1–20:1) indicated that a high amount of Rh was present in the complex.…”
Section: Resultsmentioning
confidence: 99%
“…The antimalarial potential of Rh has been previously reported. 39 , 40 In this regard, the combination that showed a better Plasmodium inhibitory performance with an IC50 of 2.5 μg/mL, DHP(G2)-MPA-Rh/hep, required a w DHP / w heparin ratio 20:1 to establish the complexes, which led to a larger amount of Rh in the sample than in the cases of DHP(G3)-MPA-Rh/hep or DHP(G4)-MPA-Rh/hep, whose respective complexation ratios were 7.5:1 and 4:1 and their IC50 was higher than 12 μg/mL. Surprisingly, the antiparasitic activities of DHP(Gn)-GMPA-Rh complexes with heparin (IC50 between 4.7 and 5.1 μg/mL) were slightly better but did not differ too much from those of the homologues without the fluorophore ( Figure 6 a), even though the ratios of complexation ( w DHP / w heparin 15:1–20:1) indicated that a high amount of Rh was present in the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Very few of these turned out to be active also on gametocytes [28,29], which prompted specific efforts in screening for compounds active on the parasite sexual stages. Only about 300,000 compounds have been so far tested in a variety of comparatively more demanding cell-based gametocyte assays, and the number of identified chemotypes inhibiting the viability of immature and/or mature gametocytes and, in some cases, blocking parasite transmission to mosquitoes is so far limited [30,31]. An observation from this endeavor is that the majority of these molecules are active also on asexual stages, which suggests that, despite the differences in the biology of the proliferative asexual stages and of the non-dividing gametocytes, few biological processes may be targetable specifically in the latter parasite stages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of these drugs is limited by their hemolytic toxicity observed in patients with glucose-6-phosphate dehydrogenase deficiency, a genetic condition with a high prevalence in regions of malaria endemicity ( 9 11 ). Extensive research is under way to discover new drugs that can effectively target Plasmodium gametocytes ( 12 14 ). Newer classes of compounds, including the spiroindolones (KAF246), imidazolopiperazines (GNF179), imidazopyrazines (KDU691), and quinoline-4-carboxamides (DDD107498), have shown potent transmission-blocking activities, and some of their closely related compounds (KAE609 or cipargamine, KAF156) have made it to clinical testing ( 15 21 ).…”
Section: Introductionmentioning
confidence: 99%